The Double Allegory of the Bon Architecte and the Mauvais Architecte by Philibert De L’Orme (diségno, 2018)
Philibert De L’Orme was one of the leading exponents of the architectural culture of the Second Renaissance in France [Blunt 1958]. A double image has been chosen, one of the best-known of the sixteenth century, which takes up the idea of the good architect, as opposed to the bad one, in an allegorical key. In the representation of the double allegory, a current, since eternal, concept emerges, intended to involve the reader in reflections that directly invest the social and political context of the practice of architecture. These works are two woodcuts, placed at the end of the treatise Le premier tome de l’Architecture (1567) [1] which documents the competencies of the architect as designer, builder and decorator. They have the characteristic of presenting the human figure and the architectural and landscape settings in an articulatedand explicit manner (read more).